Laser Proximity Sensor for Fuel-air Explosive Bomb - Singh, Durga; Verma, P.C.; Vashisth, Punit; Rawat, R.K.S.; Gupta, S.K. (Defence Science Journal, 2007)
Present study deals with design and development aspects of a diode laser proximity sensorbased on principle of optical triangulation. This sensor incorporates a laser transmitter and anoptical receiver. The beam divergence of laser transmitter and look angle of receiver are orientedin such a way that they intersect at a predetermined measuring segment. The sensor can be setto give signal output at predetermined distance from the target. Theoretical studies have beencarried out to determine the minimum power required for transmitter with a trade-off between S/Nratio, aperture of receiver optics, reflectivity of target and range requirement. The scattered laserradiation from the target in this segment is utilised in deriving a signal output to detonate thebomb at a predetermined distance from the target. The laser proximity sensor has been developedfor 3 ± 0.5 m operational range and has qualified various environmental tests and live fuel-airexplosive bomb trials.